Enhancement of thermal stability and phase relaxation behavior of chitosan dissolved in aqueous l-lactic acid: using `silver nanoparticles' as nano filler - Rana, V. K.; Pandey, Asutosh K.; Singh, Raj Pal; Kumar, B.; Mishra, Satyendra; Ha, Chang-Sik (Macromolecular Research, 2010)
Chitosan films with various compositions of silver nanoparticles were prepared by solution casting with an aqueous solution of chitosan and l-lactic acid. The chitosan/Ag nanocomposites were characterized by wide angle Xray diffraction (WAXD) and UV-vis spectroscopy. An analysis of the surface topography and size of the Ag nanoparticles (<= 100 nm) were characterized by scanning electron microscopy (SEM) and atomic force microscopy (AFM), respectively. Thermogravimetric analysis (TGA/DTA) confirmed the increase in thermal stability with increasing Ag nanoparticle content in the nanocomposites. Dynamic thermal analysis (DMA) was used to examine the phase relaxation behavior of chitosan and its nanocomposites. The conductivity of chitosan/Ag nanocomposites was considered with respect to the frequency. Contact angle measurements were used to characterize the surface twistability, surface cleanliness, and hydrophilic/hydrophobic nature of the surface.
Keywords: Chitosan; conductivity; contact angle; relaxation; silver nanoparticles

Tensile properties, cell adhesion, and drug release behavior of chitosan-silver-gelatin nanohybrid films and scaffolds - Rana, V. K.; Kushwaha, Omkar S.; Singh, RajPal; Mishra, Satyendra; Ha, Chang-Sik (Macromolecular Research, 2010)
Drug-loaded nanohybrid films and porous scaffolds were prepared using chitosan, Ag nanoparticles and gelatin using a solution casting and freeze-drying method, respectively. Gelatin was used to incorporate the cell onto the surface of the scaffolds and the nanohybrid films. 1-[2-hydroxyethyl]-2-methyl-5-nitroimidazole) (Metronidazole (MTZ) was used as a model drug. The small percentage of Ag nanoparticles in the nanohybrid films and scaffolds produced significantly higher cell proliferation and levels of drug release. The tensile properties showed improvement in strength by Ag nanoparticles reinforcement at the expense of elongation.
Keywords: carcinogenic metronidazole; cell proliferation; chitosan-Ag-gelatin nanohybrids; drug release; nano-hybrids; scaffolds